2014
DOI: 10.1039/c4ra09806d
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the electro catalytic activity of manganese ferrite through cerium substitution for oxygen evolution in KOH solutions

Abstract: Alkaline water electrolysis (AWE) is the simplest way of producing hydrogen, an attractive fuel for the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The catalyst mixed with conductive carbon at a mass ratio of 1:1 was uniformly casted on the surface of glassy carbon (5 mm in diameter) with a loading of 0.25 mg/cm 2 (More details are described in Experimental Section in SI). During the process of oxygen evolution under oxygen environment, the redox of Mn 2+ in aqueous solution to Mn 3+ -oxyhydroxide has been observed even before the oxygen generation occurred, ,, where the formed metal hydroxide would contribute to the enhanced activity. The polarization curves (Figure a) show that all the resulting MnFe 2 O 4 electrodes exhibited good performances for water oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…The catalyst mixed with conductive carbon at a mass ratio of 1:1 was uniformly casted on the surface of glassy carbon (5 mm in diameter) with a loading of 0.25 mg/cm 2 (More details are described in Experimental Section in SI). During the process of oxygen evolution under oxygen environment, the redox of Mn 2+ in aqueous solution to Mn 3+ -oxyhydroxide has been observed even before the oxygen generation occurred, ,, where the formed metal hydroxide would contribute to the enhanced activity. The polarization curves (Figure a) show that all the resulting MnFe 2 O 4 electrodes exhibited good performances for water oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, 46 we performed the initial screening of catalysts in a standard three-electrode system using various concentrations of KOH electrolytes and showed that 0.2 M cerium substitution enhances the electrocatalytic activity of MnFe 2 O 4 for OER in alkaline solution.…”
Section: Half-cell Studiesmentioning
confidence: 99%
“…Among Fe, Co, and Ni (hydr)­oxide systems, the oxides and hydroxides of Ni and Co are well-documented ones in literature. Fe alone was reported as its oxyhydroxide, where Fe is in 3+ oxidation state for efficiently catalyzing OER in alkaline solutions. , When these metals are considered alone as hydroxides in its divalent state, the Ni 2+ is the highly active catalyst than the others in the same series due to its OER favoring d-electron configuration as per the reports of Subbaraman et al However, when a combination of more than one of these metals are considered, there are many catalyst systems that had been reported to be showing better activity than Ni­(OH) 2 . Among them, the cobaltates (MCo 2 O 4 , M = Ni and Fe) and ferrites (MFe 2 O 4 , M = Ni and Co) are the frequently reported ones. Between these two, the ferrites are better than cobaltates .…”
Section: Introductionmentioning
confidence: 99%